DIGITAL TWIN APPLICATIONS IN INDUSTRIALIZED OFFSITE CONSTRUCTION: AN AI-CENTERED REVIEW - Mysak, Ihor; Mysak, Pavlo (European Science, 2025)
Industrialized offsite construction (IOC) improves efficiency, quality, and sustainability but still struggles with data fragmentation, monitoring, and coordination. This review examines studies on AI-enhanced digital twins (DTs), showing their potential